To solve the system of equations using the elimination method, we have the following two equations:
- \( 3x - 4y = -4 \) (Equation 1)
- \( x + 3y = -10 \) (Equation 2)
We can start by eliminating one of the variables. Let's eliminate \( x \). To do this, we can multiply Equation 2 by 3 so that the coefficients of \( x \) in both equations will be the same.
Multiply Equation 2 by 3:
\[ 3(x + 3y) = 3(-10) \]
This gives:
\[ 3x + 9y = -30 \quad \text{(Equation 3)} \]
Now we can set Equation 1 and Equation 3 up for elimination:
- \( 3x - 4y = -4 \) (Equation 1)
- \( 3x + 9y = -30 \) (Equation 3)
Next, we subtract Equation 1 from Equation 3:
\[ (3x + 9y) - (3x - 4y) = -30 - (-4) \]
This simplifies to:
\[ 9y + 4y = -30 + 4 \]
\[ 13y = -26 \]
Now, divide by 13:
\[ y = -2 \]
Now that we have \( y \), we can substitute it back into Equation 2 to solve for \( x \):
\[ x + 3y = -10 \]
Substituting \( y = -2 \):
\[ x + 3(-2) = -10 \]
\[ x - 6 = -10 \]
Adding 6 to both sides:
\[ x = -4 \]
The solution to the system of equations is \( (x, y) = (-4, -2) \).
So the correct answer is:
(−4,−2)